If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7y = 11 Solving 6x + 7y = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 6x + 7y + -7y = 11 + -7y Combine like terms: 7y + -7y = 0 6x + 0 = 11 + -7y 6x = 11 + -7y Divide each side by '6'. x = 1.833333333 + -1.166666667y Simplifying x = 1.833333333 + -1.166666667y
| 2(3(13)+7)=-4(3-2(13)) | | a^2-15a-30=0 | | 5x+2x+7x= | | 1.80X+1.00Y=45 | | 26x+58=6x-42 | | 100=8+a | | 5x-3=12x-11 | | 18x-1(8x-7)=67 | | Two-thirdsx=-9 | | 52=2x-6(-x-2) | | f(4z)=2x^2-3 | | 21x+6=(17-26) | | 8+x=6x-47 | | x^4-4x^3-x^2+4x=0 | | 20+x^2+8x=2x | | 3(3x-1)=4(x+3)+5x | | 4x+3=7x-1 | | (x+55)=(3x-5) | | 4(7)-12=-5(7)+51 | | x^6-47x^3-8= | | 0.60x+.05(12-x)=.10(-49) | | 2(12)+2x=2(x-2)+2(16) | | 4n+2+4=-6 | | 2(3x-3)+2(x-3)=(2x-1)+(2x-1)+2x | | x^6-47x^3-8=0 | | 3c-4c+1=5+2+3 | | 4y+3y=63 | | 3c+4c+1=5+2+3 | | (x+55)+(3x-5)=180 | | 0.5d=3 | | 2(3x-3)+2(x-3)=(2x-1)+(2x+1)+2x | | 7=-v-3+6 |